Microwave-assisted treatment for the improvement of rice flour properties and rice flour bread quality - Md Yunos, Noor Seribainun Hidayah; Hafid, Halimatun Saadiah; Omar, Farah Nadia; P. Mohammed, Mohd Afandi; Wakisaka, Minato; Mustapha, Nor Afizah; Samsu Baharuddin, Azhari (John Wiley and Sons Inc, 2024)
Modification of rice flour by microwave and its effect on bread making performance was evaluated. Rice flour having two different water content (20% and 30%) were exposed to different level of microwave power (600 W, 700 W and 800 W) with 8 min treatment time to assess its influence on amylose content, thermal properties, morphological structure, functional and crystalline structural that affect bread quality. Microwave-treated rice flour at 600 W showed notable increment in amylose content of 1.03 folds (for both 20% and 30% water content) as compared to untreated rice flour. The microwave treatment destroyed the amorphous region of the rice flour starch, whereas starch crystal structure was slightly increased after treatment. Rice flour maintained its thermal stability even after exposure to high radiation of microwave. The treated rice flour exhibited starch granules with more voids on its surface, indicating the exudation of amylose at higher temperature. The major effect of microwave treatment was observed on the bread for rice flour treated at 800 W with higher specific volume, increase in gas cells pores, softer crumb, low hardness and delayed staling as compared to untreated rice flour. The microwave-assisted treatment shows a significant potential in improving the rice flour quality led to increase the quality of bread.